Nursing Care of the People with Physical Disabilities Undergoing Flap Surgery: A Case Report - Kolcak, Bircan; Tastan, Sevinc (My University, 2022)
Nursing care provided to persons with disabilities is vital as healthcare needs of these individuals\rare higher than other patients. This case report presented information on nursing\rcare provided before and after flap surgery to a 30-year-old male with physical disability\rdue to the fall from height when he was 22 years old. The patient was admitted to the hospital\rdue to a burn wound that occurred 2.5 years ago, which resulted in loss of sensation\rin his left foot. Based on the tomography results, flap surgery was planned for the wound\rsite. In addition to urinary incontinence, constipation, and neurological problems caused by\rspinal cord injury, the patient suffered from anxiety and pain due to flap surgery, which, in\rturn, increased his need for care. We conducted face-to-face interviews and used Gordon’s\rfunctional health patterns model to identify the patient needs so that the best patient care\rcould be provided. This model guides the health professionals to collect systematic and\rstandardized data on 11 functional health patterns.
Keywords: Sağlık Bilimleri ve Hizmetleri; Hemşirelik; Cerrahi